2019
DOI: 10.3390/nano9040562
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Functionalization of Particle-Based Mesoporous Silica Films and Their Usage in Catalysis

Abstract: We report the formation of mesoporous films consisting of SBA-15 particles grown directly onto substrates and their usage as catalysts in esterification of acetic acid and ethanol. The film thickness was altered between 80 nm and 750 nm by adding NH4F to the synthesis solution. The salt also affects the formation rate of the particles, and substrates must be added during the formation of the siliceous network in the solution. Various substrate functionalizations were tested and hydrophobic substrates are requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 38 publications
(55 reference statements)
2
27
0
Order By: Relevance
“…No free particles are observed on the substrate aer ultrasonication treatment. The particle width and lm thickness decreases with an increasing salt concentration (Table 1), which is consistent with the data previously shown by Wu et al 23 The micrographs clearly shows that a vast majority of the particles are well attached to the substrate. It has been suggested that this type of lms is formed through nucleation of silica coated micelles on the hydrophobic substrate, and that the particles grow from these sites.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…No free particles are observed on the substrate aer ultrasonication treatment. The particle width and lm thickness decreases with an increasing salt concentration (Table 1), which is consistent with the data previously shown by Wu et al 23 The micrographs clearly shows that a vast majority of the particles are well attached to the substrate. It has been suggested that this type of lms is formed through nucleation of silica coated micelles on the hydrophobic substrate, and that the particles grow from these sites.…”
Section: Resultssupporting
confidence: 91%
“…This defect yields a particle that is only partly bound to the substrate and can thus inuence the particle detachment rate. The time for adding the substrates to the synthesis solution increased with decreasing salt content to gain the desired lm morphology since the material formation rate is signicantly increased by the addition of NH 4 F. 23,27 The salt affects the condensation rate of the silica precursor, and also the structure of the silica network, and therefore it is of great importance that the substrates are added during a time window in the formation of the siliceous network where micelles can nucleate onto the substrate, but prior to the micelle aggregation. In order to demonstrate that DiG lms can also be grown on rough, 3D surfaces, a DiG_0.00 was synthesized onto an alumina sand blasted silicon wafer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations